Analisis Pengaruh Penggunaan Uang Elektronik (E-Wallet) terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomi & Bisnis di Universitas Madura - Achmarul Fajar; Salwa Andina Agustin; Maulidatus Sholihah; Arikatul Faradies (PT. Hasba Edukasi Mandiri, 2026)
Advances in digital technology, particularly the use of e-wallets, have brought about significant changes in students’ transaction patterns and consumption behavior. The convenience, speed, and various promotions offered have made e-wallets increasingly popular among students, but they also have the potential to encourage consumerist behavior. This study aims to analyze the influence of e-wallet use on the consumerist behavior of students in the Faculty of Economics and Business at Madura University. The method used is a qualitative approach with a phenomenological research design. Data were collected through online questionnaires, interviews, and observations of 100 respondents selected using purposive sampling. The results indicate that e-wallet usage increases transaction frequency and encourages impulsive purchases, particularly for lifestyle-related products. Furthermore, most students do not have the habit of tracking their expenses, making it difficult for them to manage their finances. On the other hand, e-wallets also offer benefits such as transaction efficiency and easy access to digital services. Thus, the use of e-wallets has a dual impact: it serves as a tool that facilitates transactions while simultaneously having the potential to accelerate consumer behavior if not balanced with financial literacy and good self-control.